Predictors of graft outcome in renal transplant recipients with antibody-mediated rejection - Parmaksız, Ergün; Meşe, Meral; Yadigar, Serap; Bahat, Kübra Aydın (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. Active and chronic antibody-mediated rejection (ABMR) is a common cause of graft failure. Prognostic markers of this complication are not well defined. We aimed to find out the demographic, histopathological and clinical characteristics of transplant recipients who developed ABMR and evaluate the impact of these features, and anti-rejection treatment modalities on graft survival. Methods. Thirty-two patients who developed ABMR (22 male; mean age 40.59±12.52 years) were included in this study. Data were evaluated retrospectively and graft survival was analyzed. All transplant biopsies were evaluated according to Banff’s 2013 classification. Results. Among the 32 cases, 26 were transplanted from living donors. Mean serum creatinine at the time of biopsy was 1.99 ±0.09 mg/dL. Proteinuria was 1566.06±353.92 mg/day at the time of biopsy. The need for hemodialysis was significantly related with initial creatinine (p = 0.003); creatinine after three months (p < 0.001) and final creatinine (p < 0.001) as well as initial proteinuria (p = 0.005); proteinuria after three months (p < 0.001) and final proteinuria (p < 0.001). 6 cases showed diffuse C4d positivity, 26 cases showed focal c4d positivity. Five of 6 patients with diffuse C4d staining in renal biopsy were hemodialyzed at first and third months despite anti-rejection therapy (p=0.029 and 0.041, respectively). Mean survival time was 1654.67±220.40 (95% CI 1222.68-2086.66) days for focal staining C4d cases and 366.16±36.44 (95% CI 294.73-437.60) days for diffuse staining C4d cases. The difference was statistically significant (p=0.012). Two of the patients died, 15 experienced graft loss and 17 survived with functioning grafts. Mean survival time between anti-rejection treatment modalities showed no statistical significance (p=0.15) Conclusions. Serum creatinine, proteinuria at the time of biopsy, diffuse peritubular C4d staining were significantly associated with graft survival. Early diagnosis is important to improve success in the treatment of ABMR and graft survival